2012
DOI: 10.1021/jp2101144
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of O2 on Ge(100): Atomic Geometry and Site-Specific Electronic Structure

Abstract: Germanium is considered to be a potential semiconductor to replace silicon in future high-performance microelectronic devices. Yet, when compared to Si, very little is known about the surface chemistry of Ge surfaces. In this article, we report on the oxygen adsorption on Ge(100)-(2 × 1) surfaces and the related changes in the density of surface states. In particular, the adsorption geometry is examined both in reciprocal-and real-space using reflection high-energy electron diffraction and scanning tunneling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 26 publications
4
21
0
Order By: Relevance
“…26 The fact that the final oxygen coverage can increase with increasing incident energy of oxygen indicates that a new adsorption pathway may occur, resulting in novel oxide structures on Ge surfaces. Figure 2 shows LEED images before and after oxidation of the Ge(100) 22 and that the oxygen coverage is low, which is consistent with the results revealed by the quantitative uptake measurements as shown in Fig. 1.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…26 The fact that the final oxygen coverage can increase with increasing incident energy of oxygen indicates that a new adsorption pathway may occur, resulting in novel oxide structures on Ge surfaces. Figure 2 shows LEED images before and after oxidation of the Ge(100) 22 and that the oxygen coverage is low, which is consistent with the results revealed by the quantitative uptake measurements as shown in Fig. 1.…”
Section: Resultssupporting
confidence: 87%
“…These findings under low oxygen exposure conditions are supported by computational studies. 20,21 Fleischmann et al 22 reported a detailed study of the oxygen adsorption sites revealed by STM and electron diffraction experiments, describing the favorable oxygen adsorption site at moderate O 2 exposure. Despite the considerable effort to study oxidation of Ge(100) surfaces, there is a lack of information on the chemical analysis of oxidized Ge surfaces and the dependence of the absolute oxygen amount, which are relevant in the characterization of oxide structures.…”
Section: Introductionmentioning
confidence: 99%
“…Another method, an in vacuo process using supersonic molecular oxygen beams, only produces the 1+ and 2+ oxidation states in the sub-monolayer thickness [31]. The weak bonding of molecules on Ge(001) [32,33] and the confined adsorption site at the surface dimers without any insertion into the Ge backbonds [34] have rendered the four charge states unlikely to be formed at the interfacial region of Ge(001).…”
Section: Introductionmentioning
confidence: 99%
“…The partial pressure of O 2 is unreactive to the (In)GaAs substrates [35], but it is not entirely unaffected at the Ge substrate; the ALD is operating at a high pressure and it generates similar concerns for the oxygen residual. The established records of initial O 2 adsorption on Ge(001) have made their comments based on the very first work by Fukuda and Ogina two decades ago, who suggested that one of the dissociated O atoms of O 2 sits at the bridge site and the other sits at a backbond of the Ge-Ge dimer [34,36]. However, the nondissociative O 2 adsorption has also been experimentally and theoretically proposed later in the literature [33,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation is more difficult to model, due to the presence of various chemisorption processes, several competing adsorption sites, energy barriers and kinetic effects. Studies of the Ge(100) surface, which also features surface Ge dimers, act as a guide . At low coverages, DFT calculations predict that oxygen molecules dissociate and adsorb at single dimers, inserting into (or on top of) dimers and backbonds ; at intermediate coverages Ge substitution and dimer breaking is reported .…”
Section: Discussionmentioning
confidence: 99%